Successive ethanol–water fractionation of enzymatic hydrolysis lignin to concentrate its antimicrobial activity. Issue 10 (15th May 2018) - Wang, Guanhua; Xia, Yue; Liang, Benke; Sui, Wenjie; Si, Chuanling
Abstract: BACKGROUND: With the emergence of lignocellulose refining, there is an increasing interest in exploring the valuable applications for lignin due to its abundant and underused features. Originating from the physiological function of lignin in plants, this work attempted to evaluate the antimicrobial potential of enzymatic hydrolysis lignin (EHL) from a bioethanol‐derived biorefinery. RESULTS: Successive ethanol–water dissolution was employed to fractionate EHL and the antimicrobial activities of three obtained lignin fractions (F1, F2 and F3) were compared by the agar diffusion method and minimum inhibitory concentration (MIC) assays. Interestingly, the results showed that the antimicrobial activities of EHL were centralized in F1 which exhibited obviously growth inhibitory effects against two Gram‐positive ( Staphylococcus aureus and Bacillus subtilis ) and two Gram‐negative ( Escherichia coli and Salmonella enterica ) bacteria with MICs of 1, 2, 2 and 2 mg mL −1, respectively. The further characterization suggested that the better solubility and higher phenolic hydroxyl content of F1 caused by lower molecular weight were possibly responsible for the improvement of antimicrobial performance. CONCLUSIONS: Consequently, this work suggested that successive ethanol–water fractionation was an effective way to enhance the antimicrobial activity of EHL. © 2018 Society of Chemical Industry